Divergent Mechanisms Activating RAS and Small GTPases Through Post-translational Modification - Osaka, Natsuki; Hirota, Yoshihisa; Ito, Doshun; Ikeda, Yoshiki; Kamata, Ryo; Fujii, Yuki; Chirasani, Venkat R.; Campbell, Sharon L.; Takeuchi, Koh; Senda, Toshiya; Sasaki, Atsuo T. (Frontiers in Molecular Biosciences, 2021)
RAS is a primary member of RAS superfamily small GTPases and functions as a molecular switch to initialize signaling cascades involved in various cellular processes, including gene expression, cell growth, and differentiation. RAS is activated by GTP loading and deactivated upon GTP hydrolysis to GDP. Guanine nucleotide exchange factors (GEFs) and GTPase-activating proteins (GAPs) accelerate GTP loading and hydrolysis, respectively. These accessory proteins play a fundamental role in the regulation of RAS superfamily small GTPases via universally conserved G-domain, which consists of five G motifs. The Switch regions lie within the G2 and G3 motifs undergo dynamic conformational changes between the GDP-bound "OFF" state and GTP-bound "ON" state, which are important for RAS recognition by regulatory factors (GEFs and GAPs). The G4 and G5 motifs are the focus of the present work and lie outside of Switch regions. These motifs are responsible for the recognition of the guanine moiety in GTP and GDP, and contain residues that undergo posttranslational modifications that underlie new mechanisms of RAS regulation. Posttranslational modification within the G4 and G5 motifs populates RAS more in the GTP-bound "ON" state through the enhancement of intrinsic guanine nucleotide exchange or impairing GAP-mediated down-regulation. Here, we provide a comprehensive review on the mechanistic roles of the posttranslational modifications in the G4 and G5 motifs in RAS and small GTPase activation and discuss the potential applications for cancer therapy.